2017
DOI: 10.1111/jcpp.12784
|View full text |Cite
|
Sign up to set email alerts
|

Annual Research Review: Early adversity, the hypothalamic–pituitary–adrenocortical axis, and child psychopathology

Abstract: We call attention to critical gaps in the literature to highlight next steps in this research including focus on developmental timing, sex differences, stress buffering, and epigenetic regulation. A better understanding of individual differences in the adversity-HPA axis-psychopathology associations will require continued work addressing how multiple biological and behavioral systems work in concert to shape development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
329
4
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 361 publications
(348 citation statements)
references
References 157 publications
10
329
4
5
Order By: Relevance
“…Second, we examined whether developmental increases in waking levels of sex hormones are coupled with changes in waking levels of cortisol during puberty. Third, given prior evidence implicating both exposure to ELS and cortisol dysregulation in the development of mental and physical health difficulties (Koss and Gunnar, 2018), we examined whether the severity of exposure to threat-related ELS moderated the coupling of developmental increases in sex hormones with changes cortisol during puberty. Importantly, although we focused on waking levels of cortisol and sex hormones at two timepoints in development, several of our findings are consistent with those of previous studies examining the coupling of cortisol and sex hormones diurnally and in response to stress (Marceau et al, 2015b(Marceau et al, , 2014Ruttle et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we examined whether developmental increases in waking levels of sex hormones are coupled with changes in waking levels of cortisol during puberty. Third, given prior evidence implicating both exposure to ELS and cortisol dysregulation in the development of mental and physical health difficulties (Koss and Gunnar, 2018), we examined whether the severity of exposure to threat-related ELS moderated the coupling of developmental increases in sex hormones with changes cortisol during puberty. Importantly, although we focused on waking levels of cortisol and sex hormones at two timepoints in development, several of our findings are consistent with those of previous studies examining the coupling of cortisol and sex hormones diurnally and in response to stress (Marceau et al, 2015b(Marceau et al, , 2014Ruttle et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The hypothalamic-pituitary-adrenal (HPA) axis mediates physiological responses to stress (Gunnar and Quevedo, 2007), and functioning of the HPA axis has pervasive effects on mental and physical health (Koss and Gunnar, 2018). A burgeoning literature implicates atypical cortisol regulation, both diurnally and in response to stress, in the development of psychopathology (e.g., Adam et al, 2017;Colich, Kircanski, Foland-Ross, & Gotlib, 2015;Essex et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Elegant theories have been proposed to account for group differences in more subtle aspects of brain development and functioning between trauma-exposed and nontraumatised children (Gee et al, 2013;McCrory et al, 2017;Pollak & Kistler, 2002), for example highlighting potential influences on threat and reward processing that may underlie cognitive models of clinical relevance (Ehlers & Clark, 2000). Beyond the brain, group differences in hypothalamic-pituitary-adrenal (HPA) axis (Koss & Gunnar, 2018) and the immune system (Danese & Baldwin, 2017) functioning have been proposed to partly account for the long-term mental health outcomes in traumatised children. At a molecular level, epigenetic differences between adults with or without a history of childhood trauma have been proposed as a key mechanism leading to psychopathology (Klengel et al, 2012).…”
Section: How?mentioning
confidence: 99%
“…Second, disruption in HPA axis functioning can lead to emotional and behavioural abnormalities. Koss and Gunnar () discuss key neuroendocrine correlates of child psychopathology, both describing the general facts – high cortisol levels in depressed and anxious children and low cortisol levels in children with PTSD and externalising disorders – and openly reflecting on the many inconsistencies.…”
mentioning
confidence: 99%
“…First, over the past 60 years experimental research in rodents and non-human primates has shown that manipulation of the early rearing environment can result in multiple neuroendocrine abnormalities. Similarly, Koss and Gunnar (2018) argue that neuroendocrine abnormalities, such as low peripheral cortisol levels, are also often observed in children exposed to adversity. As in animal models of early life stress, findings on cortisol levels in children exposed to adversity are heterogeneous and appear to vary based on the broader social context children live in, the emotional/behavioural abnormalities observed at the time of cortisol assessment, and possibly the age at which children experienced adversity.…”
mentioning
confidence: 99%